Addressing service profit chain with artificial and emotional intelligence. Issue 6 (18th August 2022) - Wei, He; Prentice, Catherine
ABSTRACT: In view of the prevalence of artificial intelligence (AI) – powered applications in service organizations, this paper draws on service profit chain theory and proposes these applications as a service product for employees (referred to as internal customers) and customers. The outcome of which is to examine the influence of AI service quality on internal and external customer loyalty. Customer satisfaction and engagement are modeled as mediators, whereas emotional intelligence (EI) is a moderator in AI – customer loyalty relationships. Two studies were undertaken with employees and customers in Australian-based hotels to examine these relationships. The results show that AI service quality is significantly related to internal and external customer satisfaction and engagement. Both internal and external customer engagement have significant effects on customer loyalty and play a significant mediation role in the service quality – customer loyalty relationship. EI has only a significant moderation effect on the relationship between AI service quality and customer engagement for internal and external customers. Discussion and implications of the research findings are provided for researchers and practitioners.